Pathology and Muluki Aain 2074 (Journal of Pathology of Nepal, 2018)
With the implementation of the Muluki Aain 2074, there will definitely be changes how a clinician will practice medicine. The pathologists are no longer exempted from medical negligence and hence will have to change our ways of practicing too. The pathologists too have to maintain a good standard of practice, ensure that laboratory staff follow appropriate guidelines and protocols, have good communication with clinicians, ensure clear documentation of procedures and results, maintain records and subscribe to appropriate, recognized quality assurance programs. No test is perfect, so incorrect diagnoses are part and parcel of practice in pathology. But how often this matters? Different studies have shown major errors ranging from 1.5% to 5.7% globally. Error rates vary according to different variables including anatomical site to cultures, countries, legal systems and reimbursement schemes. Error in cancer diagnosis may range from 1.8% to 9.4% and 4.9% to 11.8% of all gynecological and non gynecological cases, respectively.